2021
DOI: 10.1038/s41467-021-22436-1
|View full text |Cite
|
Sign up to set email alerts
|

The Botrytis cinerea Crh1 transglycosylase is a cytoplasmic effector triggering plant cell death and defense response

Abstract: Crh proteins catalyze crosslinking of chitin and glucan polymers in fungal cell walls. Here, we show that the BcCrh1 protein from the phytopathogenic fungus Botrytis cinerea acts as a cytoplasmic effector and elicitor of plant defense. BcCrh1 is localized in vacuoles and the endoplasmic reticulum during saprophytic growth. However, upon plant infection, the protein accumulates in infection cushions; it is then secreted to the apoplast and translocated into plant cells, where it induces cell death and defense r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 66 publications
4
67
0
Order By: Relevance
“…Therefore, the remaining phytotoxic activity in the 12x mutants is due to further, as yet uncharacterized CDIPs. These include Crh1, a newly described CDIP that has been shown to be translocated via infection cushions into host cells [ 31 ], and several apoplastic CDIPs that have been recently described in fungi related to B . cinerea , Ciborinia camelliae [ 66 ], Monilinia fructigena [ 67 ] and Sclerotinia sclerotiorum [ 43 ], for which homologues exist in B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the remaining phytotoxic activity in the 12x mutants is due to further, as yet uncharacterized CDIPs. These include Crh1, a newly described CDIP that has been shown to be translocated via infection cushions into host cells [ 31 ], and several apoplastic CDIPs that have been recently described in fungi related to B . cinerea , Ciborinia camelliae [ 66 ], Monilinia fructigena [ 67 ] and Sclerotinia sclerotiorum [ 43 ], for which homologues exist in B .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel B . cinerea CDIP, called Crh1, was discovered that is translocated into plant cells, but it does not seem to contribute to infection [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among the upregulated genes there was also a homolog (BCIN_14g03930) of the S. sclerotiorum transcription factor SsNsd1 , necessary for pathogenicity and appressorium formation ( 97 ). Furthermore, upon contact with the Δ dcl2 mutant, B. cinerea upregulated several genes encoding proteins involved in chitin and cell wall synthesis, such as Bccrh1, BcchsIV, BcchsV, BcchsVI, and BcchsVII ( 98 101 ). The upregulation of BcCHSVI and BcCHSVII is of particular interest because these proteins have a role in plant infection ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the remaining phytotoxic activity in the 12x mutants is due to further, as yet uncharacterized CDIPs. These include Crh1, a newly described CDIP that has been shown to be translocated via infection cushions into host cells (Bi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A PAMP-like behavior of CDIPs was indicated by the observation that their activity was dependent on the presence of the PRR coreceptors BAK1 and/or SOBIR1 in the treated plants (Franco-Orozco et al 2017;Frías et al 2011;Yang et al 2018;Zhu et al 2017), and PRRs for Nep1/Nep2, Xyn11A and PG1/PG2 have already been identified (Albert et al 2015;Ron and Avni, 2004;Zhang et al 2014). Recently, a novel B. cinerea CDIP was discovered that is translocated into plant cells, but it does not seem to contribute to infection (Bi et al 2021).…”
Section: Introductionmentioning
confidence: 99%